Optimizing the Performance of the Violence Crime Unit of the Criminal Research Department of Klaten District Police in Disclosing Violent Theft with Transparency and Justice - Satya, Danur (Advances in Police Science Research Journal, 2024)
In this final project, the writer raised a problem regarding "How is the performance of Violence Crime Unit of Criminal Research Department of Klaten District Police in disclosing violence theft with transparency and justice?”. This final project is intended to identify how Klaten District Police disclose violence crime. This research is viewed using qualitative approach with field research type by performing observation, upholding interviews and documents study in obtaining datas. Other than that, all data used in this research are also obtained from documents and reports. This research is done by using management theory, performance measuring theory andlaw enforcement issues as well as legislation concepts and justice transparency concepts. The focus of this research is anything that isconnected to Violence Crime Unit in disclosing Violence Theft in Klaten District Police. Violence theft is having the most occurrence in Klaten District thus, the writer is interested on researching this topic. In general, ViolenceCrime Unit of Criminal Research Department of Klaten District Police has already been doing according to the rules. However, there’s still room for improvement like: 1. Lack of personals; 2. Un certified investigators; 3. Lack of budget; 4. Lack of facilities; 5. Investigation methods that are not yet fully appropriate or can be optimized.